Mutation m.15923A>G in the MT-TT gene causes mild myopathy - case report of an adult-onset phenotype - Mikko Kärppä; Laura Kytövuori; Markku Saari; Kari Majamaa (BMC, 2022)
Background: Only five patients have previously been reported to harbor mutations in the MT-TT gene encoding mitochondrial tRNA threonine. The m.15923A > G mutation has been found in three severely affected children. One of these patients died within days after birth and two had a phenotype of myoclonic epilepsy with ragged red fibers (MERRF) in early childhood. We have now found the mutation in an adult patient with mild myopathy.Case presentation: The patient is a 64-year-old Finnish man, who developed bilateral ptosis, diplopia and exercise intolerance in his fifties. Family history was unremarkable. Muscle histology showed cytochrome c-oxidase (COX) negative and ragged red fibres. The m.15923A > G mutation heteroplasmy was 33% in the skeletal muscle and 2% in buccal epithelial cells. The mutation was undetectable in the blood. Single-fibre analysis was performed and COX-negative fibres had a substantially higher heteroplasmy of 92%, than the normal fibres in which it was 43%.Conclusions: We report the fourth patient with m. 15923A > G and with a remarkably milder phenotype than the previous three patients. Our findings and recent biochemical studies suggest that the mutation m.15923A > G is a definite disease-causing mutation. Our results also suggest that heteroplasmy of the m.15923A > G mutation correlates with the severity of the phenotype. This study expands the catalog of the phenotypes caused by mutations in mtDNA.